Assessment the serum level of anti- tissue transglutaminase antibodies and HLA-DQ2 gene in Iraqi children with type 1 Diabetes Mellitus - Borhan, Noor; Al-Kabe, Muhamed (Iraqi Journal of Science, 2025)
Type 1 diabetes mellitus (T1DM) and celiac disease (CD) are two of the most prevalent autoimmune disorders affecting children and adolescents, with a notable tendency to co-occur in the same individual. This co-occurrence is thought to be attributed to the shared genetic predisposition underlying both conditions. This study aimed to evaluate the serum levels of anti-tissue transglutaminase antibodies and the impact of the human leukocyte antigen-DQ2 (HLA-DQ2) gene on their levels in diabetic pediatric populations in Wasit Province, Iraq. A total of 100 patients with type T1DM and 60 healthy individuals, both sexes, under the age of 16 years, were recruited. Blood samples (5 mL) were collected from each participant to determine the level of tTG-IgA and tTG-IgG and to detect HLA-DQ2 genes using direct ELISA and conventional PCR, respectively. Additionally, fasting blood glucose (FBG), random blood glucose (RBG), and glycated haemoglobin (HbA1C) levels were also measured. The study found a significant difference in the mean levels of tTG-IgA and tTG-IgG between patients and controls, with patients having a higher mean value of tTG-IgA than controls (16.87±72.40 versus 2.47±1.78). Similarly, tTG-IgG levels were also higher in patients (14.52±51.23 versus 2.05±2.29), although no significant correlation was found between HLA-DQ2 gene present and sample type, nor between the means of selected autoantibodies between positive and negative HLA-DQ2 gene analysis among patient groups. The study reveals a significant difference in anti-tTG autoantibodies among T1DM patients compared to healthy controls, increasing their risk of developing CD. Additionally, a high percentage of T1DM children carried the HLA-DQ2 gene, suggesting genetic screening isn't mandatory.